Machinability Investigation on Novel Incoloy 330 Super Alloy using Coconut Oil Based SiO2 Nano fluid - Ramanuj Kumar; Choudhury, Aniket Roy; Sahoo, Ashok Kumar; Panda, Amlana; Malakar, Arunjyoti (International Journal of Integrated Engineering, 2020)
Over the years, the quality of the finished surface has become the foremost prevalent owing to better output performance, reliability and life span of a machined part. Moreover, the effects of cooling and lubrication approach during the machining process play a vital role. Incoloy 330 generally used in petrochemical, chemical, power generations, thermal processing applications. This exploration focuses on the appropriate utilization of the Minimum Quantity Lubrication (MQL) based cooling approach using diverse concentrations of coconut oil based SiO2 nanofluids in the turning practice of Incoloy 330 alloy. The input variables are nanofluids concentration (Nc), feed (f) and cutting speed (Vc). The cutting insert TiAlN PVD coated cemented carbide tool is utilized to study the output responses like tool flank wear (VBc), surface roughness (Ra), material removal rate (MRR), and chip morphology. SiO2 nanofluids work effectively as tool flank wear is found to be less (VBc varies in between 0.057 mm to 0.077 mm). From ANOVA, cutting speed is found to be topmost influencing input (83.24%) for tool flank wear. Machining on the highest feed value (0.35 mm/rev) is not recommended for this work as Ra is found to be greater than 1.6 Âµm. With increasing cutting speed and feed rate, MRR increases. In each run, coiled continuous helical chips are obtained. Deformed chip thickness is found to be lower ( 0.3 to 0.74 mm) due to the application of SiO2 nanofluid through MQL which enhanced the heat dissipation thus eliminated the tendency of chip welding on the top surface of the tool. Chip reduction coefficient decreases with feed and cutting speed. Further, the TOPSIS optimization technique has been implemented to get an optimum set of cutting parameters for multiple responses and it is found to be Nc3 (0.3 % wt)-f1 (0.15 mm/rev)-Vc3 (160 m/min).